(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study aimed to systematize the variables that constitute the behavior of practicing bullying in a school environment, based on general scientific literature, through a literature review. Descriptors related to the definition and to bullying behavior were introduced in the databases, 11 studies were selected for analysis, of which 111 excerpts were analyzed. It was highlighted, in the studies, information referring to bullying behavior or to its components (antecedent stimuli, responses and consequent stimulis). Language assessment was performed to name the behaviors or its components, the criteria being: clarity, precision, conciseness and objectivity. The behaviors and its constituents was categorized, and it was identified 133 behaviors that constitute the general class, renamed from “bullying behavior” to “frequently violate a pair so that the author demonstrates its power producing damage on said pair”. The results showed the diversity of behaviors that make up the phenomenon, as well as its possible establishing and maintaining variables.